Electron Transfer Processes in Ferrocene-Modified Poly(ethylene glycol) Monolayers on Electrodes - Steentjes, Tom (Langmuir, 2017)
[Image: see text] Electrochemistry is a powerful tool to study self-assembled monolayers. Here, we modified cystamine-functionalized electrodes with different lengths of linear poly(ethylene glycol) (PEG) polymers end-functionalized with a redox-active ferrocene (Fc) group. The electron transport properties of the Fc probes were studied using cyclic voltammetry. The Fc moiety attached to the shortest PEG (M(n) = 250 Da) behaved as a surface-confined species, and the homogeneous electron transfer rate constants were determined. The electron transfer of the ferrocene group on the longer PEGs (M(n) = 3.4, 5, and 10 kDa) was shown to be driven by diffusion. For low surface densities, where the polymer exists in the mushroom conformation, the diffusion coefficients (D) and rate constants were increasing with polymer length. In the loose brush conformation, where the polymers are close enough to interact with each other, the thickness of the layers (e) was unknown and a parameter D(1/2)/e was determined. This parameter showed no dependence on surface density and an increase with polymer length.